Barriers to care in a West Bank refugee camp: a qualitative study. (March 2019) - Wispelwey, Bram P; Jawabreh, Nashat; Alazzeh, Shatha; Scales, David
Abstract: Background: Health-care delivery is fragmented owing to poorly connected health systems in the occupied Palestinian territory. Palestinian refugees are particularly vulnerable. Aida Camp in Bethlehem (with a population of approximately 6000 people) hosts refugees from 27 villages in what is now Israel. There is no clinic within Aida Camp, and health-care access is a longstanding community concern. This study aimed to elucidate refugees' perceptions of the following topics in focus group discussions, with the goal of developing interventions in a spirit of community-based praxis: (1) community health burdens; (2) access to health facilities; (3) barriers to care; and (4) engagement of community health workers as a means of addressing gaps in care. Methods: Focus group interviews with male and female refugees living in Aida Camp were conducted from December, 2016, to February, 2017. Participants were targeted using flyers and internet advertisements. Only Palestinian refugees currently living in Aida Camp and aged 18–75 years were included, and a total of 54 participants were interviewed. Sessions lasted 90–120 min, with 12 to 16 open-ended questions and facilitated discussion among eight to ten participants. Six focus groups were required to reach thematic saturation. Translated transcripts of discussions were coded and analysed. Institutional review board approval was not required for this work. Informed verbal consent was obtained for all participants. Findings: The health issues considered to be most burdensome among Aida Camp inhabitants were diabetes, hypertension, cancer, and depression, with additional focus on physical and mental trauma owing to incursions from Israeli forces. Regarding barriers to health, five principle themes were identified: military occupation, poverty, health system and provider distrust, trauma and psychological impact, and lack of a sense of agency. A community conceptual framework and flow chart were developed from the results. Interpretation: Aida Camp residents have strong opinions on and novel ideas for addressing common illnesses and barriers to healthcare. A community health worker programme is appealing to adult residents of the camp. A focus on social accompaniment may be an innovative intervention to improve management of non-communicable diseases, implement trauma-informed mental health care, and address social and political determinants of health. Funding: 1for3 and Lajee Center.